2007
DOI: 10.1007/s00464-007-9594-0
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopy in the early diagnosis and management of post-traumatic pneumothorax and hemothorax

Abstract: In light of their own experience and of reports in the literature confirming both the diagnostic and therapeutic efficacies of VATS in chest trauma with pneumothorax and/or hemothorax, the authors propose a treatment protocol prescribing its use 48 h from the traumatic event in all cases of uncontrolled air and/or blood loss. This protocol yielded excellent results, including an uneventful postoperative course, rapid resolution of the signs and symptoms of the chest problem, and no disabling sequelae (empyema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Others contend that empyema can be prevented entirely by evacuation of hemothorax in the first 7 days. 23,24 Conversely, radiographically apparent hemothorax after chest tube placement leads to a 33% rate of empyema. 25 Most authors have used the estimated volume of 500 mL, the amount needed to be seen on plain X-ray, as the entry point into studies looking at evacuation of retained hemothorax.…”
Section: Evaluation Of the Evidence Supporting Early Operative Managementioning
confidence: 99%
“…Others contend that empyema can be prevented entirely by evacuation of hemothorax in the first 7 days. 23,24 Conversely, radiographically apparent hemothorax after chest tube placement leads to a 33% rate of empyema. 25 Most authors have used the estimated volume of 500 mL, the amount needed to be seen on plain X-ray, as the entry point into studies looking at evacuation of retained hemothorax.…”
Section: Evaluation Of the Evidence Supporting Early Operative Managementioning
confidence: 99%
“…Furthermore, tube thoracostomy may bring along complications such as nonfunctioning or malposition of chest tube, wound infection, abdominal or thoracic injury and vascular trauma in 2-10% of the patients [4][5][6]. Advantages of minimally invasive surgery offered by VATS have oriented many institutions to accept this method as the preferred treatment for patients with chest trauma [14]. As noted above, 8 patients with the diagnosis of prolonged air leakage and hemothorax underwent VATS without encountering any further complications or morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many authors described the use of this technique for diagnostic (diaphragmatic lesions) and therapeutic (hemothorax in penetrating chest trauma) options (13,14). However, only in the late 1990s, due to technical advances, its use became worldwide popular and VATS gained a primary position in the care of thoracic trauma patients (7,15). Villavicencio et al (16) demonstrated that thoracoscopy may be used safely and successfully in assessment of clotted or persistent hemothorax and in empyema drainage; according to their data, 90-95% of patients with posttraumatic hemothorax are treated conservatively or with tube thoracostomy only, 20% develop later a clotted or a persistent loculated hemothorax after drainage and 40% of them require eventually a surgical procedure.…”
Section: Multiportal Vats Strategy: Basic Conceptsmentioning
confidence: 99%
“…The technical details of the procedure have been summarized by Fabbrucci et al: under general anaesthesia and with double lumen intubation, the first incision is made on the site of the thoracostomy tube and this port is used to introduce the scope. The site of the further ports (2-3-4 ports in any case) is determined from inside after the initial evaluation of the chest cavity, of the amount of blood/clots and of the bleeding source (15).…”
Section: Multiportal Vats Strategy: Basic Conceptsmentioning
confidence: 99%